Clients' experience of non‐response to psychological therapy: A qualitative analysis. Issue 2 (7th February 2018) - Radcliffe, Kay; Masterson, Ciara; Martin, Carol
Abstract: Objective: The evidence is that therapy only works for some. This study aimed to explore clients' subjective experience of non‐improvement; specifically how do participants who feel they have not benefitted from psychological therapy describe the experience and make sense of their therapy? Method: Eight people from a National Health Service Psychological Therapies Department in the UK who felt their therapy had not resulted in improvement took part in semi‐structured interviews, later analysed using interpretative phenomenological analysis. Results: Participants described a process, beginning with their difficulties, negative feelings about themselves, and initial hopes and anxieties for therapy. Once in therapy, participants described overwhelming fears of losing control and being judged. They described attempts to manage this, using self‐censoring and compliance. After therapy, while most could identify some gain, they felt disappointed and that they were having to 'make do'. The sense of not having succeeded or being sufficiently deserving of further input, in turn, reinforced participants' initial negative self‐beliefs. Conclusion: Although participants identified themselves as not having improved through therapy, the accounts suggested more complexity. All participants reported detrimental effects and accounts contained qualified, thoughtful descriptions of these experiences: participants acknowledged some gains, even though they felt that therapy had not met their expectations.